Association of Positive MRI Findings and Clinical Outcomes in Sub-acute and Chronic Phases of Pediatric Mild Traumatic Brain Injury. (4th January 2022) - Sicard, Veronik; Hergert, Danielle; Stephenson, David; Robertson-Benta, Cidney Rae; Reddy, Sharvani Pabbathi; Dodd, Andrew; Ling, Josef; Wertz, Christopher James; Pluto, Charles; Campbell, Richard; Phillips, John P.; Sapien, Robert; et al.
Abstract : Objective: This study aims to examine the rates of incidental findings (IF) and radiologic common data elements (rCDE), and to explore how these magnetic resonance imaging (MRI) findings contribute to a broad assessment of clinical outcomes (symptoms, cognitive and behavioral functioning, and quality of life) in the sub-acute (SA: ∼1 week), early chronic (EC: ∼4 months), and late chronic (LC: ∼1 year) phases of pediatric mild traumatic brain injuries (pmTBI). Background: It is unclear whether MRI findings have clinical implications following injury. Design/Methods: Two hundred thirty-three pmTBI patients and 168 HC aged 8–18 completed an MRI scan and a comprehensive clinical assessment at SA visit, with a subset completing the clinical assessment at EC (182 pmTBI; 158 HC) and LC (143 pmTBI; 141 pmTBI) visits. All MRI findings were noted by board-certified neuroradiologists and coded based on published criteria for rCDE by 2 independent researchers, who were blinded to diagnosis group. A series of 2 × 3 (group [pmTBI vs HC] × MRI findings [IF vs rCDE vs normal]) generalized linear model was conducted for outcomes at each visit. Possible and probable rCDE were pooled for the latter analyses. Results: One hundred sixty-four participants (40.9%) showed positive MRI findings (113 IF, 43 possible rCDE, 8 probable rCDE). As expected, probable rCDE was exclusively observed in pmTBI patients (Fisher's exact one-sided = 0.012), however the incidence of IF and possible rCDE was similar between groups (χ2 = 2.969; p 's = 0.085). While group effects were observed on several outcome measures, no interaction of Group × MRI findings survived the correction for multiple comparisons ( p 's > 0.01). An MRI findings effect ( p < 0.001) was observed on child-rated Children's Behavior Questionnaire at SA visit (normal > IF and rCDE; p 's = 0.009). However, this effect was no longer significant at EC and LC ( p 's = 0.439). Conclusions: Overall, the current results do not suggest that MRI findings have clinical implications or interacts with pmTBI to worsen outcomes.